Identification of optimal reference genes for gene expression normalization in human osteosarcoma cell lines under proliferative conditions - Dong, Xiaoming; Yang, Qiwei; Du, Zhenwu; Zhang, Guizhen; Shi, Chuankai; Qin, Xuyuan; Song, Yang (Frontiers in Genetics, 2022)
The molecular pathogenesis and therapeutic targets researches of osteosarcoma (OS) have well developed during last years by using various OS cell lines with reverse transcription quantitative polymerase chain reaction (RT-qPCR). However, identification of suitable reference genes of RT-qPCR for OS cell lines has not been reported. Here, we conducted the normalization research of 12 reference genes (GAPDH, ACTB, 18S, B2M, ALAS1, GUSB, HPRT1, HMBS, PPIA, PUM1, RPL-29 and TBP) for gene expression analysis in four kinds of human OS cell lines (U2OS, Saos-2, HOS and MG-63) for improving the investigation of molecular mechanisms as well as the accuracy of diagnosis and prognostic molecular targets of OS. The gene expression stability and applicability of the 12 reference gene candidates were determined using the geNorm, NormFinder and BestKeeper software. The results indicated that PUM1 and the combination of PPIA + ALAS1 were recommended as the optimal reference gene in these 4 different sources of human OS cell lines under proliferative conditions. The present study identified the most suitable reference genes and reference gene combinations for OS cell lines under proliferative conditions in order to use in gene expression profile analysis. A reliable standardized method has the potential to improve understanding of the biological mechanisms underlying OS in the future.